Miniaturized L-Shaped and U-Shaped Resonator-Based 8-Bit and 12-Bit Chipless RFID Tag - Salama, Sanaa; Tamimi, Omar; Altayeb, Muneera; AbuZahew, Ahlam (IIUM Engineering Journal, 2025)
Chipless Radio Frequency Identification (RFID) technology is a wireless technology that uses radio frequency signals (RF) to identify objects automatically. Chipless RFID tags promise a low-cost and printable solution for item tracking, authentication, and sensing in various applications, including supply chain management and the Internet of Things (IoT). In this work, two compact-sized prototypes of 8-bit chipless radio frequency identification (RFID) tags are modeled as L-shaped and U-shaped resonators. The proposed tags are printed on (14.5mm 14.5mm) Rogers RT5880 substrate with a dielectric constant, and a thickness, . The simulated RCS responses for both the L-shaped and the U-shaped 8-bit chipless RFID tags are presented. A prototype of 12 back-to-back L-shaped resonators with different lengths corresponding to resonant frequencies between 5 and 8.5 GHz is proposed to increase the chipless RFID tag capacity. The proposed 12 back-to-back L-shaped resonators chipless RFID tag is printed on (15mm 25mm) Rogers RT5880 substrate. The simulated RCS response for the compact 12-bit L-shaped resonator-based chipless RFID tag is calculated. ABSTRAK: Teknologi Pengenalan Frekuensi Radio Tanpa Cip (Chipless RFID) merupakan teknologi tanpa wayar yang menggunakan isyarat frekuensi radio (RF) bagi mengenal pasti objek secara automatik. Tag RFID tanpa wayar menawarkan penyelesaian kos rendah yang berpotensi bagi menjejak item, pengesahan, dan pengesanan dalam pelbagai aplikasi termasuk pengurusan rantaian bekalan dan Internet Benda (IoT). Kajian ini membentangkan dua prototaip bersaiz kompak; iaitu tag RFID 8-bit tanpa wayar yang dimodelkan sebagai resonator berbentuk-L dan berbentuk-U. Tag yang dicadangkan ini dicetak pada substrat Rogers RT5880 (14.5 mm × 14.5 mm) dengan pemalar dielektrik, , dan ketebalan, h = 1.575 mm. Respons simulasi RCS bagi kedua-dua tag 8-bit berbentuk-L dan berbentuk-U dibentangkan dalam kajian ini. Bagi meningkatkan kapasiti tag RFID tanpa wayar, satu prototaip yang terdiri daripada 12 resonator berturutan berbentuk-L dengan panjang berbeza dan berfrekuensi resonan antara 5 hingga 8.5 GHz telah dicadangkan. Tag RFID tanpa wayar ini dicetak pada substrat Rogers RT5880 (15 mm × 25 mm). Respons simulasi RCS bagi tag kompak RFID 12-bit tanpa wayar turut dikira.